“The Truth is in the Red Files”: An Overview of Archives in Popular Culture - Buckley, Karen (Archivaria, 2008)
This article is a personal overview of novels, motion pictures, and television series investigating how the archive and the record are being represented in popular culture. Despite the initially casual nature of the review, and the disparateness of the sources, four strong common themes became apparent: protection of the record is equated to protection of the truth; archives are closed spaces and the archival experience is an interior one for characters; records are lost and buried in archives; and the information sought in the records invariably centres around the search for self or truth. This article explores the validity of these themes, offers some reasons for their prevalence, suggests the existence of a strong dichotomy between the real and imagined narratives of the archival experience, and concludes with some thoughts on whether archivists should be concerned about this representation. RÉSUMÉ Ce texte présente un survol de romans, de films et de séries de télévision afin d’examiner comment sont dépeints les centres d’archives et les documents d’archives dans la culture populaire. Malgré le fait que cette étude semble d’abord non-scientifique, et que les sources sont disparates, quatre grands thèmes communs ressortent : la protection du document est liée à la protection de la vérité; les centres d’archives sont des endroits fermés et les personnages y vivent une expérience intérieure; les documents sont perdus et cachés dans les centres d’archives; l’information qu’on cherche dans les documents d’archives est invariablement liée à la quête de soi ou de la vérité. Ce texte explore la validité de ces thèmes, offre quelques raisons pour expliquer leur prédominance, et suggère l’existence d’une forte dichotomie entre les divers récits d’expériences aux archives vrais ou imaginés. L’auteure conclut en se demandant si les archivistes devraient se préoccuper de cette représentation ou non.